(untitled) (Sebha University Conference Proceedings, 2024)
In this study, the effect of using local mixed Libyan grasses (Halfa and Esbat) as a filler on the mechanical properties of SBR composites was investigated. This was performed by studying the effect of filler content (10, 20, 30 and 40 wt%) on mechanical properties of the composites including stress at break, elongation at break, impact strength and micro hardness. Also, a comparison study between using mixed and individual grasses has been attained. The stress at break was decreased with the addition of 10% mixed grasses, then increased as the mixed grasses content increased up to 30% and then decreased again. The incorporation of mixed grasses caused a significant decrease in the elongation at break. This decrease in the elongation at break was increased with increasing the grasses content. Impact strength was slightly increased with the addition of mixed grasses. Increasing the grasses content had no profound effect on the impact strength values of SBR composites. Hardness properties were slightly increased with the addition of mixed grasses. The optical image of SBR composite made 10% of mixed grasses content showed bad filler distribution, while composites with 20 and 30% grasses content had relatively better filler distribution. On the other hand, the image of composite with 40% mixed grasses content clearly showed the formation of filler aggregation. Mixed grasses appears to be relatively better than individual grasses (Halaf and Esbat) in order to attain composites with good strength properties. On the side, individual grasses seems to be better than mixed grasses in producing composites with relatively better impact strength and hardness properties. In both cases (individual or mixed grasses), the best content of grasses in order to provide good mechanical properties should be in the range of 20-30%. In conclusion, composites obtained from these grasses (individual or mixed)